Problematika Guru dalam Pelaksanaan Kurikulum 2013 pada Pembelajaran Geografi - Duhita, Siti Aulia; Suprapta, Suprapta; Hasriyanti, Hasriyanti (LaGeografia, 2020)
Â The research aimed to find out: 1) The form of implementing the 2013 curriculum. 2) The teacher's problem in implementing the 2013 curriculum. 3) The efforts made by the teacher to overcome the problem. This research was a qualitative research. The target in this study were 4 senior high schools in Baubau by taking 7 Geography teachers as respondents. Data collection in this study applied observation techniques, in-depth interviews, and documentation, then those were analyzed using qualitative descriptive analysis techniques. The results showed that: 1) The 2013 curriculum used graduate competencies which included aspects of attitudes, knowledge, and skills; use student-oriented learning processes; applying the Scientific Approach. 2) In the process of applying the 2013 curriculum were still many problems experienced by teachers such as; the changes of curriculum in the lesson plan; lack of function understanding on lesson plan; lack of computers mastery to develop lesson plans; lack of preparation time in designing lesson plans; Geography textbooks were still lacking in libraries; computer laboratories were no longer functioning; lack of additional facilities in class. 3) The efforts made by the teacher to overcome the problem; change the mindset to the 2013 curriculum mindset; make the principal more attentive and motivate the teacher; take part in more active socialization and training related to Curriculum 2013; improve the socialization of relationships between teachers; motivate yourself to be more excited; make the best use of reference book resources; study computer science and information technology; and strive for schools to provide and improve facilities and infrastructure to support the learning process.